Using Monopoly Game Media on Regional Cultural Diversity Material in Increasing Learning Interest of Class V Students - Rosalina, Fatma; Setiawan, Deni (Universitas Pendidikan Ganesha, 2025)
The interview results showed that in Pancasila Education learning, learning media is still limited to images, videos, and PPTs; not much concrete media has been involved. The study aimed to analyze the effectiveness of the use of Monopoly game media on the material of regional cultural diversity in increasing the learning interest of fifth-grade elementary school students. This study used a quantitative research method with a Quasi-Experimental design in the form of a Nonequivalent Control Group Design. The results showed that there was a significant difference in learning interest between students who received treatment using Monopoly game media and classes that did not receive treatment using Monopoly game media. This is based on the results of the N-Gain test, where the average percentage of the N-Gain score of the experimental group reached 84.62%, which is included in the effective category. In comparison, the control group only reached 72.73%, which is included in the fairly effective category. Thus, using Monopoly game media effectively increases the learning interest of fifth-grade elementary school students. This study implies that Monopoly game media can be used in learning activities to increase the learning interest of fifth-grade elementary school students. This certainly has an impact on students' increasing abilities.